Distribution of Cash Waqf with Debt and Receivable Mechanisms Perspective of Islamic Law and Positive Law - Firdaus , Muhammad Irkham; Pradhana , Theo Aditya; Anhar , Zulfikar Yahya (LPPPM STAI Darul Hikmah Bangkalan, 2022)
Cash waqf has great potential as a source of productive waqf funds that aim to build the people's economy and improve the welfare of the community. Productive waqf is the waqf property used in production activities and the results are distributed according to the purpose of the waqf. Many productive waqf designs have been developed by several parties engaged in the Islamic economic sector, such as the distribution of cash waqf funds for the empowerment of small and medium enterprises (SME). As has been done by the Global Action Agency for Fast Responses in Madiun, in which the distribution of waqf funds is channeled to small and medium-sized enterprises owned by the community using a debit and credit mechanism. There are pros and cons to the design of productive waqf like this because according to some opinions, waqf funds can only be produced for the social interests of the people, not for personal use, besides that according to waqf regulations in force in Indonesia, waqf assets may not be sold, given away, used as collateral, and may not be used as collateral. transferred in the form of transfer of other things. Departing from the various problems that need to be reviewed and analyzed in-depth, the researchers used a qualitative descriptive method by describing the actual state of the phenomenon of the object under study and then comparing it with the existing theory. The first stage is to collect data regarding the management and distribution practices of Cash Waqf funds at the Global Action Agency for Aksi Cepat Tanggap Madiun. The second stage is managing the data that has been obtained, then the last stage, the data obtained is tested and analyzed according to Islamic law and waqf regulations in Indonesia, and then finds the results of the research. With the source of the data obtained from the ACT Institution and the party receiving the funds used for the source and SME. The purpose of this study was to find out the practice of managing and distributing cash waqf funds at the Global Aksi Cepat Tanggap Madiun Institute and to determine their compliance with Islamic law and waqf regulations that apply in Indonesia.